Analisa mutu tablet ibuprofen generik berlogo dan generik bermerek yang diproduksi industri X di Gresik - Okta, Oktavia Noer Hidayah; Rahmawati, Dewi; Meliana, Marthy; Jalmav, Arianti; Ambari, Yani (Universitas Mataram, 2024)
Ibuprofen tablets are one of the most widely used antipyretic analgesic drugs for self-medication in pharmacies. According to the Biopharmaceutical Classification System (BCS), Ibuprofen is included in Class II or drugs with low solubility, but high permeability. This study was carried out to determine the physical quality of branded generic and branded generic ibuprofen drugs.Â Â This research was carried out by dissolution testing on ibuprofen tablets. The results obtained from the physical quality test met the specified requirements. The dissolution test showed that Q30 had dissolved more than 70%. The conclusion is that the drug meets the requirements and there is no difference between generic drugs with the logo and branded generics.